Program BOOSTER sebagai Upaya Pencegahan Perilaku Merokok pada Remaja di Desa Polorejo Kabupaten Ponorogo - Intan Septiningrum (Jurnal Pengabdian Masyarakat, 2026)
Smoking is a risky behavior and can cause various health problems in the community, such as respiratory disorders, heart disease, and cancer. In 2023, the number of active smokers in Indonesia will reach around 70 million people. The increase in the prevalence of active smokers also occurs in children and adolescents. This condition indicates the need for planned and sustainable prevention efforts. The BOOSTER program is a program that aims to increase the knowledge of adolescents in Polorejo Village about the dangers of smoking. This study is a quasi-experimental study with a one-group pre-test post-test design on the knowledge of program participants regarding the dangers of smoking. The population in this study was all residents of Polorejo Village, totaling 2,154 people. The target of the community service activities were adolescents aged 15-18 who were still in school and unmarried, totaling 88 people. Based on the average pre-test and post-test scores, it shows that there is an average increase in adolescent knowledge of 35.55, so it is concluded that the Booster Program is effective in increasing adolescent knowledge about the dangers of smoking in Polorejo Village, Ponorogo Regency.